ANALISIS YURIDIS BUKTI TIDAK LANGSUNG (CIRCUMSTANTIAL EVIDENCE) DALAM PERKARA KARTEL - TRI PRASETYO, YOGI; RAHMAT, DIDING (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The aim of this research is to examine how circumstantial evidence is used in cartel trials from a legal perspective. Because corporate actors often carry out cartels secretly, this is a violation that is difficult to prove under business competition law. In uncovering cartel agreements or actions that undermine market competition, circumstantial evidence is a very important weapon. This study examines various legal sources, such as statutory regulations, court decisions, and scientific literature, using qualitative methodology and a normative juridical approach to determine how circumstantial evidence can be used successfully in court. The research results show that circumstantial evidence is reliable and valid in cartel cases, as long as it meets the criteria of relevance, consistency and legal logic. In conclusion, the use of circumstantial evidence in cartel cases can strengthen the law enforcement process and provide justice for all parties involved.